2009
DOI: 10.1097/mbc.0b013e32832545f3
|View full text |Cite
|
Sign up to set email alerts
|

Association of inherited thrombophilia with embryonic and postembryonic recurrent pregnancy loss

Abstract: To investigate the impact of maternal-inherited thrombophilia: effects of factor V Leiden (FVL) and prothrombin gene mutation (FII 20210G>A) on the development of recurrent pregnancy loss in embryonic and postembryonic periods. A total of 153 patients were analysed for FVL and FII 20210G>A according to placenta gestation: 94 women with embryonic loss prior 10 weeks of gestation and 59 women with postembryonic (early fetal) loss occurring between 10 and 14 weeks of gestation. The control group consisted of 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 52 publications
3
13
1
Order By: Relevance
“…Some authors have suggested that FV Leiden may cause different effects depending on the gestational age and may have a greater impact after 10 weeks [15,16]. Our study lacked the power to come to clear answers here, although we saw a higher prevalence of FV Leiden in losses that occurred after 10 weeks of gestation than in those that occurred earlier.…”
Section: Resultscontrasting
confidence: 54%
“…Some authors have suggested that FV Leiden may cause different effects depending on the gestational age and may have a greater impact after 10 weeks [15,16]. Our study lacked the power to come to clear answers here, although we saw a higher prevalence of FV Leiden in losses that occurred after 10 weeks of gestation than in those that occurred earlier.…”
Section: Resultscontrasting
confidence: 54%
“…The prothrombin role on implantation was supported by experimental data for reduced infertility due to increased topical concentration of thrombin in both fallopian tubes, although the mechanism of action of locally administrated thrombin is undefined [65]. The possible impact of FII 20210 G>A on the implantation failure is also supported by the found distinct prevalence of FII 20210 G>A and FVL on early pregnancy loss [66]. In recurrent pregnancy loss before 10 week of gestation was established a more pronounced prevalence of 20210 G>A mutation compared with FVL.…”
Section: Fii 20210 G>a: Thrombin Generation Influence On Cytotrophoblsupporting
confidence: 56%
“…Data from the first trimester are particularly problematic, as few studies dif ferentiate between very early anembryonic losses and postem bryonic losses, and this may impact effect size. 72 This and other metaanalyses have been unable to find significant differences in F5 or F2 ORs based on trimester or number of losses. 43,45,46,59 Results from a recent metaanalysis 49 of unselected cohort stud ies reported a lower effect size (F5 OR: 1.52; F2 OR: 1.13) but were generally consistent with our findings (ORs 2.03 and 1.68, respectively) on fetal loss occurrence rates in carrier women.…”
Section: Discussionmentioning
confidence: 99%
“…These data confirmed an effect for both F5 and F2 (P < 0.001). More importantly, there was con cern that the casecontrol data did not provide direct evidence 99 Foka 63 Onderoglu 86 Grandone 66 Brenner 57 Krause 75 Fatini 61 Raziel 91 Agorastos 50 Glueck 64 Sottilotta 97 Hohlagschwandtner 69 Reznikoff-Etievant 92 Souza 98 Ridker 93 Hopmeier 70 Many 78 Murphy 85 Ivanov 72 Sotiriadis 96 Metz 79 Pauer 88 …”
mentioning
confidence: 99%
See 1 more Smart Citation